Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13020-021-00563-7
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing a clinically approved prescription Colquhounia root tablet to treat diabetic kidney disease via suppressing PI3K/AKT/NF-kB activation

Abstract: Background Growing clinical evidences show the potentials of Colquhounia root tablet (CRT) in alleviating diabetic kidney disease (DKD). However, its pharmacological properties and underlying mechanisms remain unclear. Methods ‘Drug target-Disease gene’ interaction network was constructed and the candidate network targets were screened through evaluating node genes' topological importance. Then, a DKD rat model induced by high-fat diet/streptozotoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In addition, triptolide and its corresponding patent medicines such as Colquhounia root tablets and Kunxian capsules have been applied for the treatment of kidney disease, including MN, diabetic kidney disease and lupus nephritis, which can restore the imbalance of the immune-inflammation system by modulating the PI3K/AKT/NF-κB/TNF-α pathway to exert beneficial effects. [36][37][38] These basic and clinical studies on the relationship between PI3K/AKT/ mTOR and MN, and the results of our study support the use of pharmacological network prediction.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, triptolide and its corresponding patent medicines such as Colquhounia root tablets and Kunxian capsules have been applied for the treatment of kidney disease, including MN, diabetic kidney disease and lupus nephritis, which can restore the imbalance of the immune-inflammation system by modulating the PI3K/AKT/NF-κB/TNF-α pathway to exert beneficial effects. [36][37][38] These basic and clinical studies on the relationship between PI3K/AKT/ mTOR and MN, and the results of our study support the use of pharmacological network prediction.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the ingredients with moderate to good-likeness (QED > 0.49) were considered as bioactive ingredients. Then, the targets of bioactive components, which were predicted by the MedChem Studio (version 3.0; Simulations Plus, Lancaster, CA, 2012) according to the structural and functional similarities of drugs, were also collected from ETCM database [ 33 ]. The targets with high similarity (structural similarity score > 0.80) were obtained for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study revealed that CRT effectively ameliorated kidney functions and renal histopathology in diabetic kidney disease through recovering the balance of immune‐inflammation system. 8 To verify its potentials against MN in a further level, we herein identified chemical and target profilings of CRT and investigated the ‘disease genes‐drug target’ interaction network combined with the in vivo and in vitro experiment validations.…”
Section: Figurementioning
confidence: 99%